Determinants of clinical severity in children with sickle cell disease and confirmed asthma - Gabriel Bafunyembaka; Mathieu Nacher; Ariel Makembi; Nadia Nathan; Narcisse Elenga (PLoS ONE, 2026)
Background Asthma is a frequent comorbidity in children with sickle cell disease and has been associated with an increased risk of acute complications, particularly vaso-occlusive crises and acute chest syndrome. However, determinants of clinical severity among children with sickle cell disease and confirmed asthma remain poorly characterized, especially in tropical settings. This study aimed to identify factors associated with clinical severity in this population. Methods We conducted an observational study among children with sickle cell disease followed in French Guiana. The analysis was restricted to children with confirmed asthma. Clinical severity was defined as the occurrence of at least two hospitalizations during the 12 months preceding evaluation for vaso-occlusive crises and/or acute chest syndrome. Factors associated with severity were assessed using univariate and multivariate logistic regression analyses. Results A total of 138 children with sickle cell disease and confirmed asthma were included, of whom 102 (73.9%) presented a severe clinical form. In multivariate analysis, no variable was independently associated with clinical severity. However, a trend toward an increased risk of severe disease was observed among children living in rural areas (adjusted OR = 1.94; 95% CI: 0.77–4.86), while a trend toward a protective effect was observed for Strongyloides stercoralis infection (adjusted OR = 0.18; 95% CI: 0.02–1.51). Allergic sensitization, although frequent (64.5%), was not associated with clinical severity after adjustment (adjusted OR = 0.66; 95% CI: 0.31–1.44). Conclusion Among children with sickle cell disease and confirmed asthma, more than one third experience severe clinical disease. No independent predictors of severity were identified. Observed trends should be interpreted cautiously and considered exploratory. These findings support a stratified approach to sickle cell–associated asthma to identify high-risk children and prevent avoidable acute complications.